Participation of the State and Civil Society in the Democracy System in Indonesia - Bayu Karunia Putra; Yana Syafriyana Hijri (Peneliti.net, 2022)
This article aims to look at the participation of the state and civil society in the democracy system in Indonesia. This topic is important and interesting, because the obligation to maintain and care for the democratic system is mandatory, considering that the current development of the state and society has raised various kinds of questions that must be answered, especially related to the democratic system in Indonesia. The research method used is the literature review method, where sources and data are obtained through the Publish or Perish, SINTA, and Goggle Scholar databases. In this method, the researcher uses a descriptive qualitative approach, where this method utilizes qualitative data and is described descriptively. The data collection technique uses a literature review technique carried out by researchers to collect valid, complete, and relevant information related to the topic of the problem that is the object of research. The data analysis technique used a literature review analysis technique, where this research was carried out by reading library sources to obtain the necessary data. The author finds that, with the existence of a democratic system, it can create national and state life in accordance with the mandate of Pancasila and the 1945 Constitution.